The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1364/ao.21.002953
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase epitaxial growth of bismuth silicon oxide single-crystal film: a new optically activated optical switch

Abstract: A single-crystalline double-layered structure of a pure (80-microm)/doped (39-microm)/pure Bi(12)SiO(20) (BSO) substrate was grown for the first time by a new liquid-phase epitaxial growth to form an optical waveguide. The waveguide layer is BSO doped with CaCO(3) (0.1 wt. %) and Ga(2)O(3) (0.197 wt. %) and has a refractive index 0.07% higher than the substrate. The optical absorption coefficients were decreased by more than 1 order of magnitude by doping with the elements Ca and Ga. The high-sensitive photoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Their experiments showed that the bismuth oxide phase at high temperature (δ-Bi 2 O 3 (FCC)) can be stabilized by SiO 2 and kept at room temperature by heating the bismuth silicon oxide to 800-1000 • C for 15-60 min and then quenching. However, their results were reproduced neither by Levin and Roth [10], who reported the phase diagram of Bi 2 O 3 -SiO 2 in 1964, nor cited by Tada et al [16] in 1982 although most of this phase diagram was conjectural. According to their phase diagram, there is no metastable δ-Bi 12 SiO 20 which could be solidified from the stoichiometric melt of 6Bi 2 O 3 • SiO 2 .…”
Section: Introductionmentioning
confidence: 76%
“…Their experiments showed that the bismuth oxide phase at high temperature (δ-Bi 2 O 3 (FCC)) can be stabilized by SiO 2 and kept at room temperature by heating the bismuth silicon oxide to 800-1000 • C for 15-60 min and then quenching. However, their results were reproduced neither by Levin and Roth [10], who reported the phase diagram of Bi 2 O 3 -SiO 2 in 1964, nor cited by Tada et al [16] in 1982 although most of this phase diagram was conjectural. According to their phase diagram, there is no metastable δ-Bi 12 SiO 20 which could be solidified from the stoichiometric melt of 6Bi 2 O 3 • SiO 2 .…”
Section: Introductionmentioning
confidence: 76%
“…The processes for epitaxial growth of Bi 12 MO 20 plates and waveguides were described in [81][82][83][84][85][86][87]. Single-crystal BSO ribbons can be produced by the Stepanov method or EFG process [88][89][90].…”
Section: Preparation Of Bi 12 Mo 20 -Based Epitaxial Structures and Pmentioning
confidence: 99%
“…In epitaxial growth, special attention must be paid to the surface condition of the substrate and the homogeneity of the hot zone on the melt surface. A similar process was used by Tada et al [82] to produce BSO layers codoped with Al and Ca. LPE growth of bismuth titanate layers, undoped and doped with V, Cu, and Ca + Ga, on (100), (110), and (111) BGO and BSO substrates (20 × 30 × 2 mm) was described by Bondarev et al [84] and Kargin et al [87].…”
Section: Preparation Of Bi 12 Mo 20 -Based Epitaxial Structures and Pmentioning
confidence: 99%